ANALISIS KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK FASE F PADA MATERI SIRKULASI DARAH DI SMA NEGERI 1 LINGGO SARI BAGANTI - Anggun Anisa, Citra; Ardi (Jurnal Biogenerasi, 2025)
The aim of this research is to determine the level of critical thinking skills of phase F students at SMA Negeri 1 Linggo Sari Baganti regarding Blood Circulation material. This research is descriptive research, with the population being phase F students at SMA Negeri 1 Linggo Sari Baganti. Samples were taken using a purposive random sampling technique, with a total sample of 40 people. The data used is primary data obtained through test instruments in the form of critical thinking skills questions about Blood Circulation material which are valid and reliable. Based on the research results, it was found that the level of students' critical thinking skills in answering blood circulation material questions in each aspect: in the interpretation aspect was in the very low category, in the analysis, evaluation, inference, explanation and self-regulation aspects in the low category. From these results, it was obtained that the average value of the critical thinking skill level of phase F students at SMA Negeri 1 Linggo Sari Baganti was 49.33% in the low category. Therefore, it is necessary to improve the critical thinking skills of phase F students at SMA Negeri 1 Linggo Sari Baganti in the low category.